Coaches’ Corrective Feedback, Psychological Needs, and Subjective Vitality in Mexican Soccer Players - Tristán, José; Ríos-Escobedo, Rosa María; López-Walle, Jeanette M.; Zamarripa, Jorge; Narváez, Miguel A.; Alvarez, Octavio (Frontiers in Psychology, 2021)
In the sport context, an essential aspect of an athlete’s development and performance happens during the interaction with the coach while receiving information on the aspects of performance that need to be modified (corrective feedback). Grounded in the Self-Determination Theory and particularly on the basic psychological needs theory, a structural equation model (SEM) was tested with the following sequence: perception of the amount of corrective feedback generated by the coach, perceived legitimacy of corrective feedback, satisfaction of basic psychological needs, and vitality in soccer players. Additionally, simple mediation and serial (double) mediation models were also tested. Participants were 377 Mexican soccer players (Maged = 16.46, SD = 1.08), who completed the instruments that evaluated the study variables. SEM results reported positive and significant variables’ interrelations in the sequence. The analysis of serial mediation model showed that the perceived legitimacy of feedback and the satisfaction of basic psychological needs fully mediated the relationship between the perception of the amount of corrective feedback generated by the coach and the perception of the subjective vitality of Mexican soccer players. Results suggest that coaches have to ensure that athletes accept the corrective feedback provided and meet their basic psychological needs. Based on SDT tenets, this research highlights the importance for coaches to be aware of the athlete’s perceptions when they are providing corrective feedback and their implications for athlete’s technical development and well-being. It is suggested to incorporate those aspects to training programs for coaches.